Modeling Country Risks: An Asian Perspective - TAN, Swee Liang (Institutional Knowledge at Singapore Management University, 2007)
This paper investigates the use of the Markov Regime Switching Model (MRSM) as a means to track changes in the levels of investor confidence. It also assesses the probabilities of a country switching between different regimes using the transition probability matrix. A maximum of three possible levels or regimes of risk – low, intermediate and high volatility regimes, is considered. From the smoothed probabilities calculated for different regimes, this paper makes inferences about timings of debt crisis. Comparing Brazil, Mexico, the Philippines and Indonesia in particular, we date the onset and subsequent dissolution of crisis-induced panic. We give interpretations of the results based on evidences of debt crisis. The objective is to investigate if there is information in the transition probability matrix and smoothed probabilities that country risk managers can use to make assessment on risk condition.